APAKAH PENILAIAN KINERJA DAN BEBAN KERJA DAPAT MEMPENGARUHI KINERJA PEGAWAI? - Herman Sjahruddin; Hasmawati Hasmawati; Farhan Alif Kadir; Ardiansyah Halim (Jurnal Bina Bangsa Ekonomika, 2024)
High performance is a demand given by the organization to employees, while performance appraisals on some occasions are not carried out in accordance with the rules and regulations that apply, on the other hand employees are given tasks that exceed their work ability. This research is oriented to explain and test the effects of assessment and workload on employee performance at the Human Resources Development Agency of South Sulawesi Province using the perceptions of 140 respondents, but there were 12 questionnaires that were not filled out completely, leaving 128 questionnaires analyzed by utilizing Partial Least Square through SmartPLS 3.2 which provides evidence if the performance appraisal has been carried out very much. Good so that it has an impact on the high performance produced, while on other causalities it can also be proven that it turns out that providing a high workload in its implementation can produce high performance